Analisis Tingkat Efisiensi Dan Pendapatan Usaha Tani Cabai Di Desa Kerinjing: (Studi Kasus Di Desa Kerinjing, Kecamatan Dempo Utara, Kota Pagaralam) - Muhammad Bahrul Ulum; Ayu Geby Gisela Syaputri; Bora Alviolesa (Inisiatif : Jurnal Dedikasi Pengabdian Masyarakat, 2025)
This study aims to analyze the level of efficiency and income of chili farming in Kerinjing Village, Dempo Utara District, Pagaralam City. Chili is one of the horticultural commodities with high economic value and plays an important role in increasing farmers’ income. However, price fluctuations and high production costs often affect the efficiency and profitability of chili farming. The research method used is a case study, with data collected through observation, interviews, and questionnaires with chili farmers in Kerinjing Village. Data analysis was carried out using farm efficiency analysis, which includes technical efficiency, price efficiency, and economic efficiency, as well as farmers’ income analysis based on the difference between revenue and production costs. The results show that most chili farmers in Kerinjing Village have managed their farming activities quite efficiently, although there are still several factors that can be improved, particularly in the use of production inputs such as fertilizers and labor. The income earned by chili farmers varies depending on land area, production level, and market selling price. In general, chili farming in Kerinjing Village is still considered profitable and feasible to be developed. Keywords : Efficiency; Income; Chili Farming; Kerinjing Village; Pagaralam.